(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A vehicle is a kind of transportation that we can use to deliver goods, materials, and livestock. But, as the years went by, automobile vehicles improved and continuously grew; this is one of the reasons why the Philippines is facing road traffic congestion. That’s why one of the solutions of the government is to put traffic enforcers in every city, barangay, municipality, and province who could help make the road much more passable by organizing the proper alignment of vehicles and making it less congested than before. The traffic enforcers are also responsible for the flow of vehicles on the highway of Novaliches Quezon City. The LGU assigned traffic enforcers to lessen the traffic in this area. .The study found that the presence of traffic enforcers had a positive impact on citing traffic violations, which is crucial for maintaining trust in law enforcement and government institutions. Effective traffic violation citation programs can promote road safety and reduce repeated traffic offenses. The study also evaluated the positive impact of traffic enforcers in guiding motorists, which was the most strongly agreed upon by the respondents. Traffic enforcers provided security and guidance, and their support was effective in promoting road safety and reducing accidents. However, the respondents were less strongly agreeable with the effectiveness of traffic enforcers in managing traffic during major events or emergencies and guiding motorists to safe and alternate routes. In terms of aiding pedestrians, the presence of traffic enforcers ensured the safe and efficient use of the roads by both motorists and pedestrians. Traffic enforcers were effective in directing traffic, helping pedestrians navigate busy intersections, and enhancing pedestrian safety. The data indicated that the respondents strongly agreed on the crucial role of traffic enforcers in aiding pedestrian safety and promoting positive traffic development in Barangay Bagbag, Novaliches, Quezon City.